Lista final de inovações e soluções do projeto AFINET - Palma, J.H.N. (2018)
Final list of innovations identified by the RAINs of the 9 regions (Portugal, Spain, Italy, France, Belgium, Poland, Hungary, Finland, UK) of the AFINET project. Presentation made during the 3rd portuguese RAIN meeting